The Holocaust & (Bio-)Ethics Education: Setting the Context - Gallin, Stacy; Bedzow, Ira (Conatus - Journal of Philosophy, 2019)
Holocaust education is important for learning how healthcare has been leveraged to influence social change in the past and how it can be used to advocate for ethical social change in the future. By understanding how medical professionals became the social and political leaders of Nazi Germany, today’s health professionals can learn how to avoid unethical politicization. By understanding how early twentieth century discourse on medico-social issues used terms and language that are similar, if not the same, as today’s debates, proponents of different sides of these debates can understand the troubling subtexts and potential consequences of their – and the opposing side’s – positions.